FREEDOM OF PRESS AND JURY TRIAL IN ISTRIA 1848/1849 - Dunja Pastović (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2015)
In Istria, as a part of the Austrian legal system, jury trial was initially introduced in the revolutionary year of 1848 only for press offenses, in the framework of aspirations for freedom of thought and expression through the press, which represented the most appropriate medium for the dissemination of new ideas and mobilization of the political masses. Trial by jury was supposed to secure impartial and objective trials, which could not be expected of professional judges due to insufficient guarantees of their impartiality. This paper examines the press-related orders and laws passed during 1848 and 1849 which regulated the freedom of press and jury jurisdiction. On the basis of an analysis of the legislative framework, jurisprudence, and the Istrian press during the examined time period, the author has decided that the introduction of the freedom of the press and jury trials for press offenses in 1848/1849 on the territory of Istria didn’t have a large practical significance.